The effectiveness of life skills–based learning in physical education - Asnela Desmannifa; Damrah Damrah; Sefri Hardiansyah; Padli Padli (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to explore the implementation of life skills–based Physical Education, Sports, and Health learning and examine the development of students’ personal and social life skills at SMK Negeri 1 Painan. A qualitative case study approach was employed involving teachers, students, and school stakeholders selected through purposive sampling. Data were collected through observations, semi-structured interviews, questionnaires, and documentation, and analyzed using the Miles and Huberman interactive model. The findings showed that life skills values were integrated through activity-based and group-oriented learning. Students demonstrated the development of responsibility, discipline, self-confidence, cooperation, communication, and empathy. Cooperation emerged as the strongest social skill, while responsibility was the most developed personal skill. However, the integration of life skills remained largely implicit, with limited reflection activities and inconsistent reinforcement by teachers. Life skills–based Physical Education, Sports, and Health learning supports students’ personal and social development. Nevertheless, more structured planning, explicit life skills objectives, and continuous reinforcement are needed to optimize its implementation in vocational education.